The effect of Training and Career Development on Job Satisfaction of the Employees of the Department of Population and Civil Registration of Pekanbaru City - Mulyani Rody Muin; Syaifora, Loveana; Alief Feisal Haznil (ProBisnis : Jurnal Manajemen, 2024)
This study aims to examine and analyze the effect of training and career development on job satisfaction of the employees of the Department of Population and Civil Registration of Pekanbaru City. This research includes quantitative research. The population in this study were all employees at the Pekanbaru City Population and Civil Registry Service. The sampling technique used is the census method so that the number of samples is 50 people. Data collection techniques in this study using a questionnaire. The data analysis technique in this study used quantitative descriptive analysis and used SPSS 20. The results of this study indicate that training and career development partially and simultaneously have a positive and significant effect on job satisfaction of the employees of the Pekanbaru City Population and Civil Registration Office. The most dominant variable affecting employee job satisfaction in this study is the career development variable. Meanwhile, the influence of training and career development on employee job satisfaction is shown by the R-Square result of .70,4%.